APLIKASI MODEL DINAMIK DAMPAK EUTROFIKASI DAN SEDIMENTASI BAGI PENGENDALIAN KERUSAKAN TERUMBU KARANG DI PERAIRAN SULAWESI SELATAN - Chair Rani; M. Natsir Nessa; Jamaluddin Jompa; Syamsuddin Thoaha; Ahmad Faizal (Jurnal Perikanan Universitas Gadjah Mada, 2014)
The aplication of dynamic model to describe the effect of eutrophication and sedimentation on coral reefs damage in a wider scope. The trial were performed in two main areas of coral reefs in South Sulawesi, namely in Spermonde Archipelago and in Sembilan Archipelago in Bone Bay. Retrieval of data include measurements of water quality (nitrate and phosphate concentration) and the rate of sedimentation. While collecting of ecological data, namely macroalgae cover, coral reef cover, and species of herbivores and its abundance. Data was collected on monthly for 4 months at six stations/islands. The data was taken at two points on each island as replicates. Oceanographic data were taken every month, while the ecological data were taken at the end of the study. Nutrients concentration (nitrat and phosphat) and sedimentation rate were measured in laboratory. The result of the model test showed that the developed model is valid and broad-spectrum and therefore can be applied to other areas already impacted by eutroﬁ cation and sedimentation. The results of the execution of the model shows that all stations on the island leads Phase shift, namely the dominance of macroalgae cover in the future (about 2-4years in the future).